The Challenges of Governing Urban Food Production across Four European City‐Regions: Identity, Sustainability and Governance. Issue 1 (29th March 2018) - Reed, Matthew; Mettepenningen, Evy; Swagemakers, Paul; Garcia, M. Dolores Dominguez; Jahrl, Ingrid; Koopmans, Marlinde E.
Abstract : The development of food production in cities has raised some important questions about the governance of these activities and the role of city‐regions. In this paper through four European case studies– Bristol (UK), Ghent (Belgium), Vigo (Spain), and Zurich (Switzerland) –we consider the ways in which food is governed at the city level. Our case studies demonstrate the role played by citizens in urban food and the challenges this brings to city‐region governance. Through horizontal networking, being inspirational to other cities and citizens, communicating their demands and successes very clearly, urban food activists have raised significant questions about how cities are governed. Using the creation of localized identities, which are inclusive and embracing but rooted in their city, these food activists are looking to a future controlled by a democratic impulse rather than the technocracy of professional city managers. This paper uses a range of Weberian influenced theory to explore the topic of urban agriculture not as one simply about environmental performance but of the construction of new civic identities.